2015
DOI: 10.1016/s1872-2067(15)60831-2
|View full text |Cite
|
Sign up to set email alerts
|

Highly oxidized Pt species stabilized inside carbon nanotubes for asymmetric hydrogenation

Abstract: The chemical state and its influence on Pt species in or outside of the channels of CNTs and the effect on the asymmetric hydrogenation of α-ketoester were investigated. XPS analysis showed that 13% Pt species in a highly oxidized state (Pt 4+ ) were stabilized inside the channels in the presence of Na + . There were more highly oxidized Pt species inside the CNTs than outside. The highly oxidized Pt species promoted the interaction between the nanoparticle and chiral modifier, which is crucial for high enanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Compared with the outer spaces, the internal nanospaces of CNTs act as a nanoreactor for phenol hydrogenation. Guan et al [38] reported that the CNTs as a nanoreactor function not only to enrich the molecules inside the channels, but also to stabilize the higher oxidative state of Pt. Since the reuse performance of the supported noble metal catalysts is one major factor in practical application, we also examined the catalytic performances of the recycled catalysts (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the outer spaces, the internal nanospaces of CNTs act as a nanoreactor for phenol hydrogenation. Guan et al [38] reported that the CNTs as a nanoreactor function not only to enrich the molecules inside the channels, but also to stabilize the higher oxidative state of Pt. Since the reuse performance of the supported noble metal catalysts is one major factor in practical application, we also examined the catalytic performances of the recycled catalysts (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Metallic species confined in carbon nanotubes (CNTs) are prepared by several methods. Dispersed metallic species in the channels of CNTs can be achieved by loading metallic precursors using classical impregnation methods [129][130][131][132] or chemical vapor deposition approaches. 133 Other more complexes synthesis involve the thermal annealing of MOFs bearing the desired metal.…”
Section: Confining Metal Active Species In Carbon Nanotubesmentioning
confidence: 99%
“…13). 129,131 Additionally, CNTs possess electron-deficient internal walls due to charge transfer from the…”
Section: Selective Hydrogenation Reactions Over Metals Confined In Cntsmentioning
confidence: 99%
See 2 more Smart Citations